2014
DOI: 10.1088/1674-1137/38/4/047005
|View full text |Cite
|
Sign up to set email alerts
|

Progress on the construction of the 100 MeV/100 kW electron linac for the NSC KIPT neutron source

Abstract: Yun-Long(池云龙), PEI Shi-Lun(裴士伦) 1) , PEI Guo-Xi(裴国玺), WANG Shu-Hong(王书鸿), CAO Jian-She(曹 建社), HOU Mi(侯汨), LIU Wei-Bin(刘渭滨), ZHOU Zu-Sheng(周祖圣), ZHAO Feng-Li(赵风利), LIU Rong(刘熔), KONG Xiang-Cheng(孔祥成), ZHAO Jing-Xia(赵敬霞), DENG Chang-Dong(邓昌东), SONG Hong(宋洪), LIU Jin-Tong(刘晋通), DAI Xu-Wen(戴旭文), YUE Jun-Hui(岳军会), YANG Qi(杨奇), HE Da-Yong(何大勇), HE Xiang(贺 祥), LE Qi(乐琪), LI Xiao-Ping(李小平), WANG Lin(汪林), WANG Xiang-Jian(王湘鉴), MA Hui-Zhou(麻惠洲), ZHAO Xiao-Yan(赵晓岩), SUI Yan-Feng(随艳峰), GUO Hai-Sheng(郭海生), MA Chuang-Xin(马创… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Fig.6 The gun current signal from oscilloscope 3.5A electron beam was successfully obtained when we applied 120kV high voltage at repetition rate 1~10Hz, the flat top width of the pulsed power supply output is about 3.5us as shown in Fig. 6 [5] .…”
Section: Beam Testmentioning
confidence: 90%
“…Fig.6 The gun current signal from oscilloscope 3.5A electron beam was successfully obtained when we applied 120kV high voltage at repetition rate 1~10Hz, the flat top width of the pulsed power supply output is about 3.5us as shown in Fig. 6 [5] .…”
Section: Beam Testmentioning
confidence: 90%
“…In the NSC KIPT (National Science Centre, Kharkov Institute of Physics and Technology, Ukraine), a 100-MeV electron linac is being constructed by IHEP [5]. For that linac, a standard bunching system was adopted.…”
Section: Beam Dynamics Requirementmentioning
confidence: 99%
“…The PB, the B and the accelerating structure can be tuned independently to get the appropriate beam phase and energy spectrums at the bunching system exit, so that a clean bunch without any satellite electrons in each RF period downstream the Chicane system can be obtained [5]. With 120 kV / 0.85 A electron beam emitted from the gun, a beam with 600 mA pulsed current, 2.7 μs pulse length and < ± 4% peak-to-peak energy spread can be acquired at the linac exit [5]. To make the bunching system more compact but not fairly deteriorate the beam performance, the studies by using the HAS with the schematic layout shown in Fig.…”
Section: Beam Dynamics Requirementmentioning
confidence: 99%
“…To satisfy the energy spread requirement (<±4% pto-p) at the 100 MeV/100 kW linac exit [6], the hybrid bunching system should be able to produce similar energy spectrum as the nominal design, which is appropriate for the downstream collimation process realized by a dedicated chicane system with a collimator deployed. It should be possible to obtain a 600 mA electron beam (∼70% efficiency) after collimation (at the chicane system exit).…”
Section: Beam Dynamics Simulationmentioning
confidence: 99%